Effects of a Multi-ingredient Beverage on Recovery of Contractile Properties, Performance, and Muscle Soreness After Hard Resistance Training Sessions. Issue 7 (July 2020) - Naclerio, Fernando; Larumbe-Zabala, Eneko; Cooper, Kelly; Seijo, Marco
Abstract : Abstract: Naclerio, F, Larumbe-Zabala, E, Cooper, K, and Seijo, M. Effects of a multi-ingredient beverage on recovery of contractile properties, performance, and muscle soreness after hard resistance training sessions. J Strength Cond Res 34(7): 1884–1893, 2020—Carbohydrate-protein–based supplements have been proposed for maximizing postexercise recovery. This study compared the effects of postworkout supplementation ingesting a multi-ingredient (MTN) vs. carbohydrate alone (CHO) on the recovery of muscle function and perceived of delayed onset of muscle soreness (DOMS) after hard resistance workouts. In a double-blinded, crossover design, 10 resistance trained men (26.9 ± 7.4 years) performed 2 identical 5-day intervention periods while ingesting either MTN or CHO. The subjects performed one workout per day during the first 3 days. Thereafter, they were assessed 1, 24, and 48 hours after the completion of the third workout session. Primary outcome was tensiomyography (muscle displacement [Dm], contraction time [Tc], and contraction velocity [Vc]) of the vastus medialis (VM) and biceps femoris long head (BFLH). Secondary outcomes were performance and DOMS. At 24 hours, both conditions decreased ( p < 0.05) Dm (MTN −1.71 ± 1.8, CHO −1.58 ± 1.46 mm) and Vc (MTN −0.03 ± 0.03, CHO 0.03 ± 0.04 m·s −1 ) in the VM. At 48 hours, all tensiomyography variables were recovered under the MTN while remained depressed ( p < 0.01) in CHO (VM, Dm 1.61 ± 1.60, Vc −0.04 ± 0.04 m·s −1 ; BFLH, Dm 1.54 ± 1.52, Vc −0.02 ± 0.02 m·s −1 ). Vertical jump performance decreased in CHO, but not in MTN. Although both conditions decreased upper-body strength and power at 1 hour, values returned to baseline in 24 hours for MTM while needed 48 hours in CHO. DOMS similarly increased at both 24 and 48 hours in both conditions. Compared with the ingestion of only carbohydrates, postworkout multi-ingredient supplementation seems to hasten recovery of muscular contractile properties and performance without attenuating DOMS after hard resistance workouts. Abstract : Supplemental Digital Content is Available in the Text.